MODAL SOSIAL DALAM USAHA CAPTIKUS DI DESA RANOLAMBOT KECAMATAN KAWANGKOAN BARAT - Martini Frinli Lomboan; Melsje Yellie Memah; Charles Reijnaldo Ngangi (Sam Ratulangi University, 2019)
Â Â This study aims to examine the social capital of the network, beliefs and social norms in captikus industries in Ranolambot Village, Kawangkoan Barat District, Minahasa Regency. This study uses primary data obtained through interviews using a questionnaire to 30 farmers who were chosen purposively. Secondary data was taken from the Village Office and other sources from the internet through Google searching to obtain books, articles and theses that discuss social capital in the agricultural processing industry. Data analysis using Likert scale and analyzed descriptively. The results of the study show that: (1) Social networks are in the Fairly Good category because networks with people outside the village are still lacking because when capturers and farmers in Ranolambot Village sell captics outside the village as well as outside companies, they must use intermediaries so that captikus will be sold. (2) Trust is in the Fairly Good category because Trust between the host and the captikus farmer must be further enhanced by mutual trust because when there are farmers who first take the money to the captikus the money should be replaced with the captikus but there are other farmers who do not return that money because it has moved to another colector trader. (3) Social norms are in the category of Good because the colector and the capticus farmer abide by all the rules that apply both fellow farmers and the colector with the government in the village, for example in the case of a captikus permits, before the capticus colector makes an effort to become their host used to make a license to collect capticus. *eprm*